2016
DOI: 10.1242/jcs.173666
|View full text |Cite
|
Sign up to set email alerts
|

Germline deletion of huntingtin causes male infertility and arrested spermiogenesis in mice

Abstract: Human Huntingtin (HTT), a Huntington's disease gene, is highly expressed in the mammalian brain and testis. Simultaneous knockout of mouse Huntingtin (Htt) in brain and testis impairs male fertility, providing evidence for a link between Htt and spermatogenesis; however, the underlying mechanism remains unclear. To understand better the function of Htt in spermatogenesis, we restricted the genetic deletion specifically to the germ cells using the Cre/loxP sitespecific recombination strategy and found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In addition, urinary retention, leading to overdistension of the urinary bladder was observed in 70% of TM-treated cKO males at the time of sacrifice, but was never observed in control males or in TM-treated cKO females. As expected, global loss of Htt expression also resulted in testicular atrophy [ 16 , 23 ], which could be already observed 3 months after Htt elimination ( S6B Fig , S7 Table ), but did not grossly affect other peripheral organs ( S7 Fig and S8 Table ).…”
Section: Resultsmentioning
confidence: 53%
“…In addition, urinary retention, leading to overdistension of the urinary bladder was observed in 70% of TM-treated cKO males at the time of sacrifice, but was never observed in control males or in TM-treated cKO females. As expected, global loss of Htt expression also resulted in testicular atrophy [ 16 , 23 ], which could be already observed 3 months after Htt elimination ( S6B Fig , S7 Table ), but did not grossly affect other peripheral organs ( S7 Fig and S8 Table ).…”
Section: Resultsmentioning
confidence: 53%
“…Functional annotation clustering analysis showed that 62 proteins were annotated with sexual reproduction ( S8 Table ). Of these, genes corresponding to the following phenotypes were present: PLCZ1 for oocyte activation [ 28 ], PLCD4 and PRSS21 for the acrosome reaction [ 29 , 30 ], and HTT for sperm head maturation [ 31 ] ( Fig 5A ). Western blot analysis confirmed that these four proteins were decreased in Zfy1/2 -DKO sperm compared to in WT sperm (n = 2) ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Elongating spermatids reduce nuclear volume through DNA compaction during spermiogenesis, and defects in DNA compaction can ultimately impact sperm nuclear morphology [ 34 ]. In this regard, deletion of the mouse ortholog of the human huntingtin gene, Htt , resulted in arrested spermatogenesis at the post-meiotic phase, partly due to disturbed translation and DNA packaging [ 31 ]. This suggests that the abnormal head phenotype of Zfy1/2 -DKO sperm could be caused by a downregulation in HTT expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in both YAC128 mice and HD patients failed to demonstrate mHTT aggregation in testis, but showed high levels of expression of WT and mutant HTT in brain and testis relatively to other organs [ 17 ]. Results in Hdh knockout mouse models suggested also an essential function of HTT in regulating spermatogenesis [ 47 , 48 ]. If changes in maturing cells in the germinal epithelium and testis pathology are associated with mHTT and HTT expression in testis, one would expect that the lack of changes in germinative cell number and testis morphology in BACHD rats, is paralleled by a low expression of mHTT in testis or at least a lower expression of mHTT in testis than in brain where pathological alterations are known in this model already at three months of age [ 20 ].…”
Section: Discussionmentioning
confidence: 99%